1967
DOI: 10.1002/ange.19670790102
|View full text |Cite
|
Sign up to set email alerts
|

Die heterolytische Fragmentierung als Reaktionstypus in der organischen Chemie

Abstract: [3] J. Muthieu, A . Allais u.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0
4

Year Published

1969
1969
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(33 citation statements)
references
References 133 publications
0
29
0
4
Order By: Relevance
“…Gleichung (a) zeigt, daß AG° nun um den Unterschied der freien Ionisationsenthalpie der Produkte und der Reaktan- Die Umkehr der hier diskutierten Additionsreaktionen ist die Grob-Fragmentierung [32] . In qualitativer Übereinstim mung mit Gleichung (e) wird die Fragmentierung kovalenter Produkte dann beobachtet, wenn bei dem Zerfall ein gut stabilisiertes Carbenium-Ion (großer pA^-Wert) gebildet…”
Section: Ag°h = Ag° -(Ag°r -Ag%) (A)unclassified
“…Gleichung (a) zeigt, daß AG° nun um den Unterschied der freien Ionisationsenthalpie der Produkte und der Reaktan- Die Umkehr der hier diskutierten Additionsreaktionen ist die Grob-Fragmentierung [32] . In qualitativer Übereinstim mung mit Gleichung (e) wird die Fragmentierung kovalenter Produkte dann beobachtet, wenn bei dem Zerfall ein gut stabilisiertes Carbenium-Ion (großer pA^-Wert) gebildet…”
Section: Ag°h = Ag° -(Ag°r -Ag%) (A)unclassified
“…maxima at 2730, 1730, 1680, 1640, 1585, and 1575 cm-l, nuclear magnetic resonance signals at 0.32 and 2.25 z (singlet). Although a fragmentation reaction (8) in compound (11) could in principle take place in two different ways, fragmentation in the sense of the dotted arrow in formula (11) was in fact not observed.Reduction of 12 with lithium aluminium tritert-butoxy hydride in tetrahydrofuran to alcohol (13) (89 % yield) was followed by conversion with methanesulfonyl chloride in pyridine to 14 (97 %) and by a treatment of the mesylate with lithium 'See reference (7) 13 R = OMchloride in boiling acetone to give the chloride (15) in 84% yield. Spectroscopic and analytical evidence has indicated that treatment of 15 with sodium cyanide does not give the desired nitrile (I$), but in fact involves the addition of the cyanide ion to the P-position of the r,p-unsaturated ketone with the concomitant formation of a cyclopropane ring.…”
mentioning
confidence: 98%
“…maxima at 2730, 1730, 1680, 1640, 1585, and 1575 cm-l, nuclear magnetic resonance signals at 0.32 and 2.25 z (singlet). Although a fragmentation reaction (8) in compound (11) could in principle take place in two different ways, fragmentation in the sense of the dotted arrow in formula (11) was in fact not observed.…”
mentioning
confidence: 98%
“…1) Thus, enol ether 159 cleanly rearranged at high temperature to diene 160. 2 Eight to ten-membered-rings, which are common in natural products [35], can be prepared by heterolytic fragmentation of bicyclic systems [36]. The latter can be formed by several methods among which RCM is one of the most efficient.…”
mentioning
confidence: 99%